Metagenomic assessment and next-generation sequencing (NGS) in indoor air microbiome analysis: A short review of current evidence - Nor Husna, Mat Hussin; Hajar Fauzan, Ahmad (AIP Publishing, 2025)
Indoor air quality is a critical aspect of the built environment, profoundly impacting human health and well-being. The indoor air microbiome, a complex ecosystem comprising bacteria, fungi, viruses, and other microorganisms, plays a pivotal role in indoor air quality. Next-generation sequencing (NGS) and metagenomic assessments have revolutionized the study of the indoor air microbiome, enabling researchers to explore microbial diversity and functionality with unprecedented depth and precision. This systematic review aims to provide a comprehensive analysis of the application of NGS and metagenomic techniques in profiling the indoor air microbiome. By synthesizing a vast body of research, the review elucidates the methodology underlying these innovative technologies and examines the diversity of microorganisms in indoor environments by using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) method. Factors influencing microbial composition including geographical location, building design, and human occupancy are explored together with their implications for air quality and human health. Furthermore, the review discusses the implications of indoor air microbiome research for public health and environmental management.